2022
DOI: 10.1038/s41409-022-01761-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-relapse cytopenias following allogeneic stem cell transplantation, a case based review

Abstract: The development of non-relapse cytopenias (NRC) is a relatively common occurrence post allogeneic stem cell transplant (alloSCT). Whilst there have been attempts to classify post alloSCT cytopenias by transplantation groups, ambiguity of definitions in prior publications compounded by a lack of availability of high-quality evidence, provide challenges to clinicians attempting to manage these complex patients. In this review we describe 3 cases of NRC, (1) Graft Failure with graft rejection representing cytopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…In such cases, no or minimal donor chimerism may be associated with graft rejection, whereas complete donor chimerism may mean poor graft function. In addition, there are cytopenic patients with mixed chimerism who may develop bone marrow failure, graft rejection, or resolution of their cytopenia [ 75 , 76 ]. Risk factors for graft failure include the use of RIC and/or CBT, the presence of HLA antibodies, low infused cell number, viral infection, and various other causes [ 62 ].…”
Section: Chimerism Analysis Guiding Management Of Allo-hsct Recipientsmentioning
confidence: 99%
See 3 more Smart Citations
“…In such cases, no or minimal donor chimerism may be associated with graft rejection, whereas complete donor chimerism may mean poor graft function. In addition, there are cytopenic patients with mixed chimerism who may develop bone marrow failure, graft rejection, or resolution of their cytopenia [ 75 , 76 ]. Risk factors for graft failure include the use of RIC and/or CBT, the presence of HLA antibodies, low infused cell number, viral infection, and various other causes [ 62 ].…”
Section: Chimerism Analysis Guiding Management Of Allo-hsct Recipientsmentioning
confidence: 99%
“…Most studies involving salvage second allo-HSCT for graft failure are retrospective and small with heterogeneity in conditioning regimens and graft selections as well as timing of onset; these studies presumably include primary and secondary graft failure. In general, OS after the second allo-HSCT for graft failure is poor due to high rates of treatment-related mortality associated with infections [ 76 ]. However, recent studies have shown acceptable OS after salvage second allo-HSCT, including CBT or allo-HSCT from haploidentical related donors [ 78 , 79 , 80 , 81 , 82 , 83 ].…”
Section: Chimerism Analysis Guiding Management Of Allo-hsct Recipientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor graft function is a syndrome of severe, life-threatening peripheral cytopenias despite >95% donor engraftment ( 8 ). Analysis of our transplant centre data (929 patients, alloSCT 2000–2016) has shown that PGF occurs in 13% of patients undergoing alloSCT, with a mortality rate of 60% in those without bone marrow (BM) recovery ( 9 ).…”
Section: Introductionmentioning
confidence: 99%